OPTIMALISASI SARANA PRASARANA KUNCI MENINGKATKAN PENDIDIKAN ISLAM - Azzahra, Fauziah; Ulum, Siti Raudhatul; Mirnawati, Liana; Maryati, Sulis (Cahaya Ilmu Bangsa Institute, 2024)
Education is the main key to unlocking human potential and abilities in living life. To achieve educational goals, various factors need to be considered, including the provision of complete facilities and infrastructure. Effective management of facilities and infrastructure in schools is very important for the smooth teaching and learning process. Management planning for Islamic education facilities and infrastructure is an important part in realizing quality Islamic education. Careful and focused planning will have an impact on the effectiveness and efficiency of utilizing Islamic education facilities and infrastructure, so that in the end the goals of Islamic education can be achieved. The principles are important guidelines in Islamic education facilities and infrastructure.